2008
DOI: 10.1159/000117823
|View full text |Cite
|
Sign up to set email alerts
|

Role of Medial Pancreatectomy in the Management of Intraductal Papillary Mucinous Neoplasms and Islet Cell Tumors of the Pancreatic Neck and Body

Abstract: Background/Aim: Medial pancreatectomy has been applied as a safe and effective alternative in benign diseases located in the pancreatic neck or body. However, the role of this procedure remains controversial. We investigate outcomes using this method in 14 patients. Methods: Fourteen consecutive patients underwent medial pancreatectomy. The surgical indications, postoperative outcomes, and pathologic characteristics were retrospectively analyzed. Results: Among 10 patients with intraductal papillary mucinous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Considering that the pancreas in patients who underwent CP is generally a soft pancreas with normal-caliber pancreatic duct, and surgeons need to manage 2 resectional margins of the pancreas at one time, if each resectional margin of the remnant pancreas has the same risk of pancreatic fistula it may not be surprising that pancreatic leak or fistula rate may exceed the commonly accepted range following distal pancratectomy or pancreaictoduodenectomy. The higher occurrence of pancreatic fistula following CP was also demonstrated in other large volume studies (range 25–50%) [12,14,20,21,22,23,24,25]. However, theoretically, pancreatic leaks after CP with pancreaticogastrostomy can be managed safely by conservative management alone, because pancreatic juices are not exposed to bile enzyme activation, as occurs after pancreaticoduodenectomy, which means pancreatic leak following central pancreatectomy may naturally possess a lower risk of auto-digestive activity [21].…”
Section: Discussionsupporting
confidence: 76%
“…Considering that the pancreas in patients who underwent CP is generally a soft pancreas with normal-caliber pancreatic duct, and surgeons need to manage 2 resectional margins of the pancreas at one time, if each resectional margin of the remnant pancreas has the same risk of pancreatic fistula it may not be surprising that pancreatic leak or fistula rate may exceed the commonly accepted range following distal pancratectomy or pancreaictoduodenectomy. The higher occurrence of pancreatic fistula following CP was also demonstrated in other large volume studies (range 25–50%) [12,14,20,21,22,23,24,25]. However, theoretically, pancreatic leaks after CP with pancreaticogastrostomy can be managed safely by conservative management alone, because pancreatic juices are not exposed to bile enzyme activation, as occurs after pancreaticoduodenectomy, which means pancreatic leak following central pancreatectomy may naturally possess a lower risk of auto-digestive activity [21].…”
Section: Discussionsupporting
confidence: 76%
“…To minimize heterogeneity among studies, only the 21 studies (19 retrospective and 2 prospective) involving more than ten patients undergoing CP were included in the systematic review of overall outcome of CP, yielding 656 patients ( Table ). Most patients were women (435 of 656, 66·3 per cent).…”
Section: Resultsmentioning
confidence: 99%
“…(6,8,49,50) However, good oncological outcomes were reported in several studies, for the branch type intraductal papillary mucinous neoplasms with minimally-invasive or in situ adenocarcinoma, when a margins negative resection could be accomplished. (17,51,52) Uncommon indications for a CP are chronic pancreatitis (17,29) and pancreatic trauma. (53) Large published series have shown that the main indications for a CP were represented by the neuroendocrine tumors (8%-36%), serous cystadenomas (20%-44%), mucinous cystadenomas (8%-35%), and branch type intraductal papillary mucinous neoplasms (12%-35%) (table 1).…”
Section: Indications and Contraindications For A Central Pancreatectomentioning
confidence: 99%